Aplikasi Zat Pengatur Tumbuh Asam Giberelat (Ga3) dan Pengaruhnya terhadap Pertumbuhan dan Produksi Bawang Merah (Allium ascalonicum L.) di Desa Datar Kecamatan Sumbang pada Musim Hujan - Ignatius Drajat Krisna Jati; Rostaman Rostaman; Eny Rokhminarsi (UM Purwokerto Press, 2022)
The purpose of this research was to determine the effect and the best concentration of GA3 growth regulator on the growth and yield of shallots. The research was carried out in the rice fields of Datar Village, Sumbang District, Banyumas Regency, from February to April 2022. This study was a non-factorial field experiment using a randomized block design with 5 treatments and 5 replications. The treatment was the concentration of GA3 with 5 levells, namely 0 ppm, 250 ppm, 500 ppm, 750 ppm and 1000 ppm. The conclusion of this study is the application of GA3growth regulator affected increasing the number of tillers leaf area, bulb number/clump, fresh bulb weight/clump, dry bulb with dry leaves weight/clump, absolute dry bulb weight/clump, yield/plots and yield/hectare. Application of 500 ppm GA3growth regulator showed the best growth and yield of shallot. It was indicated by the number of tillers, leaf area and yield/hectare of 11.54 plants, 1162.18 cm2 and 16.54 ton, respectively